2015
DOI: 10.1186/s13567-015-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

The within host dynamics of Mycobacterium avium ssp. paratuberculosis infection in cattle: where time and place matter

Abstract: Johne’s disease or paratuberculosis, caused by Mycobacterium avium subsp. paratuberculosis (MAP), occurs in domestic and wild animals worldwide, causing a significant economic loss to livestock industries. After a prolonged incubation time, infected cattle shed MAP bacilli into feces and spread the disease to an uninfected animal population. It is largely unknown how (or whether) the interplay between the pathogen and the host immunity determines timing of shedding after the long incubation time. Such informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 99 publications
0
84
0
2
Order By: Relevance
“…A histopathological study in Indian buffalo revealed inflammation of lymph node and intestine, thickening and corrugation of small intestine and granulomatous inflammation (Sivakumar et al, 2006). A study conducted by Koets et al (2015) revealed that thickening and corrugation of intestine along with enlargement of mesenteric and lymph nodes were prominent in diseased animals. This corrugation and thickening of mucosa may be due to infiltration of mononuclear cells, i.e., epithelioid macrophages infiltration in mucosa and in submucosa (Maxie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A histopathological study in Indian buffalo revealed inflammation of lymph node and intestine, thickening and corrugation of small intestine and granulomatous inflammation (Sivakumar et al, 2006). A study conducted by Koets et al (2015) revealed that thickening and corrugation of intestine along with enlargement of mesenteric and lymph nodes were prominent in diseased animals. This corrugation and thickening of mucosa may be due to infiltration of mononuclear cells, i.e., epithelioid macrophages infiltration in mucosa and in submucosa (Maxie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of the disease is poorly known. The organism is usually assumed to pass through the lumen of the small intestine and move towards the Peyer's patches via Microfoldcells (M cells) of the follicle associated epithelium, soon this is phagocytized by macrophages (Koets et al, 2015). MAP has ability to survive and replicate within macrophages in the intestine and in the lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…paratuberculosis (MAP), which results in serious economic losses worldwide in farmed livestock such as cattle, sheep, and goats (Bannantine et al, 2014). It is characterized by chronic enteritis, progressive debilitation and poor response to therapy with a long subclinical phase, during which shedding of bacteria in faeces may be present (Sweeney et al, 2012;Koets et al, 2015). It is caused by Mycobacterium avium subspecies paratuberculosis (MAP) that has also been suspected for causing regional ileitis or Crohn's disease (CD) in humans (McNees et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the opening article Koets et al [1] review the immunobiology of bovine paratuberculosis. The in vivo pathogenesis studies have been largely based on data obtained from cross-sectional studies, mainly with a primary diagnostic focus.…”
mentioning
confidence: 99%